Intestinal Occlusion: Consequence or Diagnosis? - Martínez, Bertha Zenaida Acevedo; Sánchez, Morelos Adolfo García; Valdés, Karen Stefany Cortés; Larios, Zuri Sadai Grez; Nova, Alondra Guadalupe Flores; Hernández, Pamela Navarro; Lavin, José Camilo Morales; Vázquez, Juan Pablo Rayas; París, Romero Ángeles Bruno (British Journal of Healthcare and Medical Research, 2024)
Introduction: Intestinal occlusion is a very common pathology in health services, both in admission to the Emergency Department and in the definitive treatment and/or complication of surgical practice in Surgery. Its definition is per se underestimated. Objective: Presentation of a case. Method: A 39-year-old female with intestinal obstruction was a carrier of an intragastric balloon for more than 2 years without follow-up. With frank data of acute abdomen, exploratory laparotomy was performed, removing the foreign object by enterotomy. Discussion: The prevalence of obesity has multiplied in recent decades, which has led to an increase in bariatric surgery and other endoscopic modalities, which were developed for the first time around 1985 with the intragastric balloon, which today is the most widely used endoscopic modality, which therefore, surgical treatment of complications should be considered, if necessary, in case of perforation and/or gastrointestinal obstruction. Conclusions: Intestinal occlusion is not a definitive surgical diagnosis, but a consequence of another real disease.